Rh(III)‐Catalyzed C‐2 Alkylation of Indoles followed by a Post‐Synthetic Modification via the Ugi Reaction - Marcelo Augusto Pereira Januário; Demetrius P. deSouza; Prof. Dr. Julio Zukerman‐Schpector; Prof. Dr. Arlene G. Corrêa (ChemistryOpen, 2023)
Abstract Indole derivatives substituted at the C‐2 position have shown important biological activities. Due to these properties, several methods have been described for the preparation of structurally diverse indoles. In this work, we have synthesized highly functionalized indole derivatives via Rh(III)‐catalyzed C‐2 alkylation with nitroolefins. Under the optimized condition, 23 examples were prepared with 39–80 % yield. Moreover, the nitro compounds were reduced and submitted to the Ugi four‐component reaction, furnishing a series of new indole‐peptidomimetics in moderate to good overall yields.